2005
DOI: 10.1007/s10745-005-7681-1
|View full text |Cite
|
Sign up to set email alerts
|

Historical Ecology on Sandoy, Faroe Islands: Palaeoenvironmental and Archaeological Perspectives

Abstract: We present palaeoenvironmental, geomorphological, archaeological, and place-name data which allow a holistic assessment of the history of landscape change on Sandoy, Faroe Islands, especially in terms of the changes that occurred in response to the colonization of the island by humans. In contrast to other situations in the North Atlantic region, there is considerable continuity in the patterns and processes of landscape evolution across the initial Lawson et al. settlement horizon. Many of the characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 44 publications
(44 reference statements)
1
60
0
1
Order By: Relevance
“…Further investigations have been carried out in the area to the north of the church revealing extensive settlement remains which may belong to the earliest settlement within this holding, with calibrated radiocarbon age ranges (1 standard deviation) of A.D. 785-875 and A.D. 900-960 , and these, along with the dates from Toftanes on Esturoy (Vickers et al, 2005), are currently the earliest settlement dates in the Faroes. Excavations are continuing at the site, and these, in part, are reported elsewhere Woollett et al, 2004;Lawson et al, 2005). The archaeological remains found at Sandur including the only silver coin hoard found in the islands, buried around A.D. 1090, suggest high status and strong links with the outside world.…”
Section: Archaeological Evidencementioning
confidence: 66%
See 2 more Smart Citations
“…Further investigations have been carried out in the area to the north of the church revealing extensive settlement remains which may belong to the earliest settlement within this holding, with calibrated radiocarbon age ranges (1 standard deviation) of A.D. 785-875 and A.D. 900-960 , and these, along with the dates from Toftanes on Esturoy (Vickers et al, 2005), are currently the earliest settlement dates in the Faroes. Excavations are continuing at the site, and these, in part, are reported elsewhere Woollett et al, 2004;Lawson et al, 2005). The archaeological remains found at Sandur including the only silver coin hoard found in the islands, buried around A.D. 1090, suggest high status and strong links with the outside world.…”
Section: Archaeological Evidencementioning
confidence: 66%
“…Recent zooarchaeological investigations at the site of Junkarinsfløttur in Sandur show that birds were widely exploited at an early stage (Lawson et al, 2005). It is still too soon to say whether this investigation is representative for all the islands.…”
Section: A New Look At Early Settlement Distributionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is clear from the relatively small amount of palynological research carried out in the Faroes (e.g., Edwards and Craigie, 1998;Hannon et al, 2001;Jóhansen, 1985;Lawson et al, 2005) that the dominant natural vegetation prior to human occupation was sedge-heath-grassland, and woodland seems to have been of minor importance. Any agricultural migrants to the archipelego would be limited to the coastal strip and valley bottoms-"the land they can till is only a frill or a flounce of green below the knees of their cloud-capped mountains" (Linklater, 1948, p. 16).…”
Section: Location and Physical Contextmentioning
confidence: 99%
“…Jørgensen (1978) described the morphology of 9 mainly rock slides, originating from late or post glacial time, in Suðuroy (the southernmost island of the Faroe Islands), three of which have later been redefined as rock glaciers (Humlum, 1998). In a multidisciplinary study by Lawson et al (2005) it was found that from 2000-4000 yr BP, a general slope destabilization in the Faroe Islands occurred, most likely due to climate changes. When analyzing 4 soil pits on a slope at Klaksvík on the island Borðoy Christiansen et al (2007) identified app.…”
Section: Introductionmentioning
confidence: 99%